A situational judgment test of personal initiative and its relationship with performance - BLEDOW, Ronald Joachim (Institutional Knowledge at Singapore Management University, 2009)
Although situational judgment tests have been found to be valid predictors of performance, they have rarely been used to measure particular constructs. In this study, we apply the situational judgment test method to the measurement of personal initiative, a construct defined as situated action. We used respondents' situated preferences in mental simulations of work scenarios as formative indicators of their overall level of personal initiative at work. Results from a validation study showed that the situational judgment test of personal initiative (SJT-PI) had adequate validity and complemented a Likert-type self-report measure of personal initiative in predicting behavioral criteria. Situated preferences for personal initiative were hypothesized to be proximal predictors of actual behavior and were accordingly found to mediate the relationship between generalized self-efficacy, felt responsibility, and actual behavior. Furthermore, situated preferences for personal initiative could be differentiated empirically from organizational citizenship behavior. We conclude that situational judgment tests are a promising method for measuring personal initiative and may be a general means of improving the validity of measurement in organizations.